Impact Of Poultry Manure And Agricultural Lime On Acidic Soil Of Fiji (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this study is to prove whether Poultry Manure (PM) is a suitable organic alternative to Lime Stone (LS) to neutralize acidic soil in Fiji. A greenhouse experiment was conducted to compare the effects of poultry manure and agricultural Lime on soil fertility on selected chemical properties of an acidic soil series of Fiji. The pots received seven treatments, an unamended control, 5.0, 7.5 and 1.0Mg/ha-1 PM and lime. All treatments were replicated three times and were arranged in the greenhouse in the randomized design. The pots received 200 mL water continually for four weeks. The results indicated that the application of PM increased the soil pH, %N, exchangeable Ca, Mg, K and P levels amended soil compared to CaCO3. The study clearly demonstrate that the fertility of acidic soil can be corrected by either (CaCO3) or PM addition. It is evident that PM maybe used as an alternative to CaCO3. The conventional liming materials such as calcium carbonate are not only scarce and expensive. There is needed to focus on development of locally adapted indigenous and sustainable way of managing soil acidity.